2015
DOI: 10.1186/s12863-015-0207-y
|View full text |Cite
|
Sign up to set email alerts
|

A colorectal cancer prediction model using traditional and genetic risk scores in Koreans

Abstract: BackgroundGenome-wide association studies have identified numerous single nucleotide polymorphisms (SNPs) as associated with colorectal cancer (CRC) risk in populations of European descent. However, their utility for predicting risk to CRC in Asians remains unknown. A case-cohort study (random sub-cohort N = 1,685) from the Korean Cancer Prevention Study-II (KCPS-II) (N = 145,842) was used. Twenty-three SNPs identified in previous 47 studies were genotyped on the KCPS-II sub-cohort members. A genetic risk scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…For example, Cho et al (39), reported a higher GRS that was associated with CRC (OR, 2.57; 95% CI, 1.89, 3.49) using thirteen SNPs. In addition, Jung et al (40) in a casecohort study, demonstrated that participants in the highest quartiles of the genetic risk score had an increased risk of CRC (hazard ratio, 2.65; 95% CI, 1.43 to 4.91) compared with those in the lowest quartile using seven SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cho et al (39), reported a higher GRS that was associated with CRC (OR, 2.57; 95% CI, 1.89, 3.49) using thirteen SNPs. In addition, Jung et al (40) in a casecohort study, demonstrated that participants in the highest quartiles of the genetic risk score had an increased risk of CRC (hazard ratio, 2.65; 95% CI, 1.43 to 4.91) compared with those in the lowest quartile using seven SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic characteristics of the study populations A majority of the risk prediction models have been developed in United States of America [18,22,33,38,39,42,44,45,48,49,50,51,53,54] followed by Korea [14,17,20,35]. Three models have been developed in China [16,23,36] and Japan [40] while, Netherlands [25,26], Germany [21], Taiwan [32,46] and United Kingdom [31,34] have developed two models each.…”
Section: Questionnairementioning
confidence: 99%
“…The questionnaires range from those with only one or two simple questions to those with detailed questions on factors such as diet, physical activity, alcohol and smoking habits and past medical facts. Three purely genetic models have used only a blood test for genetic biomarkers [32,34,39], while thirteen models have used data from a questionnaire and the results of blood tests for genetic biomarkers and other biochemical tests [16,17,20,27,31,35,47]. One model has obtained data both from a questionnaire and medical records [15].…”
Section: Development Of the Modelsmentioning
confidence: 99%
See 2 more Smart Citations